2017
DOI: 10.5664/jcsm.6670
|View full text |Cite
|
Sign up to set email alerts
|

Three-Generation Family With Congenital Central Hypoventilation Syndrome and Novel PHOX2B Gene Non-Polyalanine Repeat Mutation

Abstract: PHOX2B non-polyalanine repeat mutation (NPARM) in patients with congenital central hypoventilation syndrome (CCHS) is generally considered to be associated with full-time ventilator dependence and severe autonomic nervous system dysfunction. We report a three-generation family with four individuals possessing a novel PHOX2B NPARM (c.245C > T) with variable phenotypes. This mutation was inherited in an autosomal dominant pattern with variable penetrance. The affected family members with CCHS have a milder pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 10 publications
1
21
0
3
Order By: Relevance
“…In closing, improved clinical recognition of CCHS and access to PHOX2B molecular testing has both facilitated earlier diagnosis and generated an expanded phenotypic spectrum for PHOX2B‐ related disorders. As reported here, these cases illustrate an expanding phenotypic spectrum for PHOX2b NPARMs to include individuals with sufficiently mild respiratory abnormalities that infants may first present with seemingly isolated HD and/or neuroblastoma (Cain et al, ; Kasi et al, ; Unger et al, ). From these cases and collation from the literature, we suggest that initiation of mechanical‐assisted ventilation should not be a forgone conclusion in all patients diagnosed with CCHS in infancy.…”
Section: Discussionmentioning
confidence: 60%
“…In closing, improved clinical recognition of CCHS and access to PHOX2B molecular testing has both facilitated earlier diagnosis and generated an expanded phenotypic spectrum for PHOX2B‐ related disorders. As reported here, these cases illustrate an expanding phenotypic spectrum for PHOX2b NPARMs to include individuals with sufficiently mild respiratory abnormalities that infants may first present with seemingly isolated HD and/or neuroblastoma (Cain et al, ; Kasi et al, ; Unger et al, ). From these cases and collation from the literature, we suggest that initiation of mechanical‐assisted ventilation should not be a forgone conclusion in all patients diagnosed with CCHS in infancy.…”
Section: Discussionmentioning
confidence: 60%
“… 1 However, NPARM mutations have variable expressivity and incomplete penetrance. 13 , 83 , 84 Some patients have been shown to present with central apneas without hypoventilation, 85 mild hypoxemia, 85 or need for assisted ventilation only during sleep 13 , 84 while others are asymptomatic and are identified only by genetic testing through an affected family member. 13 , 83 , 85 Cain et al 84 described two patients with nonsense pathogenic variant in exon 1 of the PHOX2B producing an N terminally truncated protein presenting with milder phenotype (need for ventilatory support only during sleep and without HSCR or peripheral neuroblastic tumors).…”
Section: Phox2b and Respiratory Controlmentioning
confidence: 99%
“…Two siblings had sleep hypoxemia, anisocoria, HSCR, and characteristic facial features (one sibling did also have a congenital heart disease), while their mother had sleep apnea, anisocoria, and a congenital heart disease but without HSCR or malignancy. 85 In 2017, Kasi et al 13 reported a three-generation family with four individuals possessing a novel PHOX2B NPARM (c.245C>T) with variable phenotypes. Two of the family members were ventilator dependent only during sleep, with one of them requiring a cardiac pacemaker.…”
Section: Phox2b and Respiratory Controlmentioning
confidence: 99%
See 2 more Smart Citations